Survey of four important viruses causing abortion in cattle in aegean region - Murat Kaplan; Abdurrahman Anıl Çağırgan; Kemal Pekmez; Fatih Arslan; Gülnur Kalaycı (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the study was to investigate the role of Bovine herpesvirus- 1 (BHV-1), Schmallenberg virus (SBV), , Akabane virus (AKAV) and pestivirus in cattle abortion cases in the Aegean Region of Turkey between 2015 and 2019. Materials and Methods: In this study, 204 bovine abortions that occurred in the Aegean region of Turkey between the years 2015 and 2019 were investigated. While BHV-1, SBV, and pestivirus were examined with real-time PCR, AKAV was examined with nested-PCR. Results: In our study, 25 (12.3%) of the samples analyzed were positive for pestiviruses, 1 (0.5%) was positive for Akabane, and 1 (0.5%) was positive for BHV-1. SBV was not detected. According to these results, the viral agent causing most abortions in the Aegean region was found to be pestivirus. The most abortion-related material was sent to the lab in 2018, followed by 2019, 2017, 2016, and 2015. Conclusion: Based on the results of this study, future evaluations should consider the cattle abortion agents detected in the Aegean region, and control and monitoring studies should be established.